Pusat Pelatihan Meditasi Arama Maha Buddha Di Kota Makassar - Dian Riski Amalia; Abdul Rahman (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This research is entitled Maha Buddha Arama Meditation Training to Increase Obedience in Worship in Makassar. This research has a formulation of the problem namely (1) What is the process when conducting meditation training for Buddhists in the city of Makassar, (2) What are the benefits for Buddhists in conducting meditation training in the city of Makassar, (3) What is the impact after completing the meditation training process in Makassar? Makassar city. Which aims to find out how the process takes place after undergoing meditation training and the impact of this meditation training. The results of this study indicate that there are several meditation training processes at the Arama Maha Buddha Meditation Training Center: (1) The most important meditation process is to have good intentions first so that the meditation process goes according to our wishes. (2) the benefits of meditation for the meditation participants themselves are that the mind is much more focused and gets inner peace. (3) The impact after undergoing meditation is that we feel more aware and aware of what we are doing.